Peradaban dan Pendidikan Islam pada Masa Dinasti Umayyah: Sejarah, Perkembangan, dan Relevansinya di Era Modern - Vijra Islamul Hafiz; Nurzena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
History may be defined as a reconstruction of human life dynamics that includes numerous changes, events, and occurrences across time. In the framework of Islamic culture, the advent of the Umayyad Dynasty was significant since it signaled the continuity of rule following the Khulafaur Rasyidin period. This caliphate lasted from 661 to 750 CE, with its administrative seat in Damascus, before expanding to Cordoba, Spain, from 756 to 1031 CE, becoming known as the Caliphate of Cordoba. The Umayyad Dynasty derived its name from Umayyah ibn Abd Shams, the ancestor of its founder, Muawiyah ibn Abu Sufyan. From the standpoint of Islamic education, understanding Islamic teachings must be done thoroughly and integratively, covering all facets of human existence including spiritual, social, and moral aspects. Islam is ultimately a religion of mercy for all creation (rahmatan lil 'alamin) and should not be linked to extremism.